The Use of Cohesive Devices in Research Paper Conference to Achieve Texts Coherence - Perwari Melati Akmilia; Abdurrachman Faridi; Zulfa Sakhiyya (English Education Journal, 2022)
This paper employs discourse analysis to investigate cohesive devices and coherence in research articles. The research was based on a purposive random sampling of 10 research articles from the 8th ELTLT Conference 2019. The text analyzed in this paper includes the abstract, introduction, research methodology, findings and discussions, and conclusion. We seek to find out grammatical and lexical cohesion as conceptualized by Halliday and Hasan's (1976) concept, i.e., reference, substitution, ellipsis, conjunction, reiteration, and collocation. Furthermore, we discover the relation among research articles to achieve coherence by employing logical relations that highlight Thornbury's (2005) theory. According to the findings, the authors used cohesive devices in the creation of their writing product. From a total of 1955 clauses in 224 paragraphs, it was determined that almost all types of cohesive devices are used throughout the text. The conjunction of addition was the most frequently used cohesive device in the texts. Our findings demonstrate that authors engage the additional information to create a text without changing the context in the previous clause or sentence. However, there was no evidence of verbal ellipsis in the texts we examined. It was because the authors did not use both lexical verbs and modal operators. In conclusion, a cohesive device binds text together and bridges the gaps to avoid misleading context and achieve text coherence. Further studies need to explore the use of cohesive devices as a tool to improve the quality of writing.